2020
DOI: 10.1111/cob.12414
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: Impact of obesity and diabetes on disease severity

Abstract: Summary The coronavirus disease 2019 (COVID‐19) pandemic is straining the healthcare system, particularly for patients with severe outcomes requiring admittance to the intensive care unit (ICU). This study investigated the potential associations of obesity and diabetes with COVID‐19 severe outcomes, assessed as ICU admittance. Medical history, demographic and patient characteristics of a retrospective cohort (1158 patients) hospitalized with COVID‐19 were analysed at a single centre in Kuwait. Univariate and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 20 publications
(13 reference statements)
2
50
0
1
Order By: Relevance
“…The authors also found that the number of patients needing ICU admission did not differ from that with CV disease (20.4%) although it was higher than that with chronic lung disease (14.3%) or at an immuno-compromised status (15.5%). A report in Kuwait states that individuals with DM and obesity are more prone to ICU admission as the COVID-19 pandemic continues (46).…”
Section: Morbidity Of Sars-cov-2 Infection In Diabetic Patientsmentioning
confidence: 99%
“…The authors also found that the number of patients needing ICU admission did not differ from that with CV disease (20.4%) although it was higher than that with chronic lung disease (14.3%) or at an immuno-compromised status (15.5%). A report in Kuwait states that individuals with DM and obesity are more prone to ICU admission as the COVID-19 pandemic continues (46).…”
Section: Morbidity Of Sars-cov-2 Infection In Diabetic Patientsmentioning
confidence: 99%
“…The association between obesity and the severity of COVID-19 has been reported in several studies. However, it is important to demonstrate that the association was also observed in Japanese patients who are generally less obese than patients in Europe and the United States [14,15]. As regards underlying diseases, previous reports showed that comorbidities such as hypertension, diabetes mellitus, and cardiovascular disease correlate with COVID-19 mortality.…”
Section: Discussionmentioning
confidence: 93%
“…(10,11) In particular people with diabetes and obesity are reportedly at greater risk for severe COVID-19 symptoms. (17,(30)(31)(32)(33)(34) Therefore, in the COVID-19 era, the prevention and treatment of diabetes and other lifestyle diseases assumes even greater importance. Conversely, during the COVID-19 era, the stay-at-home policy has led to significant changes in people's life-styles.…”
Section: Discussionmentioning
confidence: 99%